Creencias y prácticas de autoevaluación del aprendizaje vigentes en los procesos de formación profesional desarrollados en el CIDE durante el 2007 - Ovares Barquero, Sandra (2008)
This article identifies beliefs and practices of self-learning existing processes developed in the CIDE during 2007. It is based on a research project with two groups of informants both academics from CIDE, that during the decade of the 90 participated in the experience of self-learning, some of themas teachers and other as students. Current practices being carried out by academics in the field of self-reporting of apprenticeships in the CIDE, show that they attach great importance to this process in the lesson and agree on the necessity to implement this process in concrete terms, that because, experiences become isolated initiatives that do not fall within any policy, guideline or orientation openly raised by the community CIDE. The beliefs of the participants with regard to the possibility of implementing self-evaluation processes of learning in the training that develops the CIDE, highlight the need for scholars to train group of academics and students in this field and also create more spaces for student involvement. Moreover, scholars believe that the self-assessment of learning is a strategy for developing metacognitive processes and reflective, which is considered a core importance in the training provided by the Centre.